“Vaccinating a child is upon the woman”: implications for improving uptake for the recently introduced second dose of measles-containing vaccine based on a rapid community assessment in Uganda - Adelline Twimukye; Nessa Ryan; Flavia Vivian Najjuma; Yvette Wibabara; Judith Nanyondo; Shillah Nakato; Maria Sarah Nabaggala; Ciara Sugerman; Daniel Kadobera; Rita Atugonza; John Kamulegeya; Joseph Magoola; et al. (Frontiers in Global Women's Health)
BackgroundCaregiver barriers to accessing immunizations are a key factor influencing childhood vaccination. In preparation for the rollout of the second dose measles-containing vaccine (MCV2) in Uganda in October 2022, we aimed to identify possible barriers specific to female caregivers that could influence MCV2 implementation and suggest initiatives to facilitate MCV2 uptake.MethodsIn September 2022, we conducted a rapid community assessment in 18 districts in Uganda. We conducted key informant interviews with 17 district health managers and 18 community leaders, and 18 focus group discussions, one in each district, with caregivers of immunization-eligible children. We conducted a rapid analysis based of debriefing notes and in-depth thematic analysis of translated transcripts. Data were analyzed using NVivo version 12, wherein we used the framework analysis approach to define and structure codes deductively and inductively to identify themes. We mapped themes onto the socio-ecological model to examine factors that influence immunization at individual, household, community, and health system level.ResultsWe found that individual, household, and health system factors influenced childhood vaccination and could be potential barriers to MCV2 uptake. At the individual level, female caregiver's heavy workload and limited decision-making power hindered their ability to take children for vaccination, with mothers often relying on fathers and depended on men for transport costs to immunization centers. At the household level, participants mothers were primarily responsible for taking children to vaccination centers, while fathers were less involved in child health. Health workers often gave preferential treatment to fathers over mothers at the health facility when they brought the child in for vaccination Participants suggested that approaches that ensure the involvement of fathers, other family members and mother-to-mother peer groups could address the barriers specific to female caregivers.ConclusionRole differentiation between female and male caregivers affect childhood vaccination practices within communities in Uganda, potentially exacerbating challenges in accessing vaccines for children in the second year of life. Integrating interventions responsive to specific caregiver needs and that improve family participation may improve childhood vaccination in Uganda.